2016
DOI: 10.4236/aim.2016.64029
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram of <i>Escherichia coli</i> and <i>Pseudomonas</i> Strains Isolated from Wastewater Generated by an Abattoir as It Journeys into a Receiving River

Abstract: Untreated wastewater from abattoir operations contains nutrients and other components that aid the growth of microorganisms especially bacteria. They also serve as a habitat for potentially pathogenic bacteria which might be a source of public health concern. The study was carried out to determine the antibiotics susceptibility profile of Gram-negative bacteria (Pseudomonas and Escherichia coli) to selected antibiotics. Wastewater samples were collected from ten different sampling points and cultured on Eosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The current study revealed that the majority (88.6%) of bacterial isolates were multidrug resistant (MDR) which is in line with study conducted in China (85.5%) [13], in Ibadan, Nigeria (94.8%) [25], in Northwestern Ethiopia (81.5%) [17], in Mekelle, Northern Ethiopia (76.5%), in Addis Ababa Ethiopia (64%) [22], and in Arba Minch, Ethiopia (70.4%) [23]. The patterns of MDR antibiogram in the current study showed that: all (100%) isolates of Shigella spp., 93.5% of E. coli, 92.8% of Salmonella spp.,88.9% of Klebssiella spp.…”
Section: Discussionsupporting
confidence: 88%
“…The current study revealed that the majority (88.6%) of bacterial isolates were multidrug resistant (MDR) which is in line with study conducted in China (85.5%) [13], in Ibadan, Nigeria (94.8%) [25], in Northwestern Ethiopia (81.5%) [17], in Mekelle, Northern Ethiopia (76.5%), in Addis Ababa Ethiopia (64%) [22], and in Arba Minch, Ethiopia (70.4%) [23]. The patterns of MDR antibiogram in the current study showed that: all (100%) isolates of Shigella spp., 93.5% of E. coli, 92.8% of Salmonella spp.,88.9% of Klebssiella spp.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, cefotaxime (5 µg) was the most effective antibacterial agent against Escherichia coli isolates. Recent investigations have reported the multiresistance of Escherichia coli to antibiotics [40]. Similar observations have been reported by Coleman [37].…”
Section: Antibiotic Resistance Testsupporting
confidence: 83%
“…Phenolic contents for these extracts ranged between 100.69±3. 40 Merr. & L. M. Perry, Cinnamomum zeylanicum Blume, Laurus nobilis L., Juniperus foetidissima Willd., Allium sativum L. and Myristica fragrans Houtt) against the gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Similar antibiotic resistance profile was also detected by Odjadjare et al [5] where high level resistance was observed against the penicillins (90%-100%), cephems (70%), sulphamethoxazole (90%) and rifampin (90%). Also, Falodun and Adekanmbi [22] revealed 100% resistance to ceftazidime and piperacillin.…”
Section: Discussionmentioning
confidence: 99%